Palladium Nanoparticles Supported on Nitrogen‐Doped Carbon Nanofibers: Synthesis, Microstructure, Catalytic Properties, and Self‐Sustained Oscillation Phenomena in Carbon Monoxide Oxidation. Issue 7 (21st May 2014) - Stonkus, Olga A.; Kibis, Lidiya S.; Yu. Podyacheva, Olga; Slavinskaya, Elena M.; Zaikovskii, Vladimir I.; Hassan, Abdelwahab H.; Hampel, Silke; Leonhardt, Albrecht; Ismagilov, Zinfer R.; Noskov, Aleksandr S.; Boronin, Andrey I.
Abstract The oxidation of CO over Pd nanoparticles supported on carbon nanofibers (CNFs) and N‐doped carbon nanofibers (N‐CNFs) has been studied. Investigation by scanning transmission electron microscopy together with electron energy‐loss spectroscopy revealed that Pd nanoparticles are located on the N‐CNFs surface patches that have a high concentration of N atoms. The N‐doping of CNFs was shown to change the electric conductivity of N‐CNFs and redox properties of Pd, which thus determines the self‐oscillatory behavior of the catalysts during CO oxidation, the type of oscillations, and the conditions of their generation. Mechanisms that underlie the effect of N in N‐CNFs on the electronic state of Pd as well as the occurrence of two types of oscillation mechanisms—the known redox mechanism and the mechanism related to Pd intercalation into graphene layers—are discussed.